An awareness-dependent mapping of saliency in the human visual system - Wang, Lijuan; Huang, Ling; Li, Mengsha; Wang, Xiaotong; Wang, Shiyu; Lin, Yuefa; Zhang, Xilin (NeuroImage (Orlando, Fla.), 2022)
•Saliency is mapped as a graded manner with awareness.•Saliency is mapped as a non-graded manner without awareness.•The graded manner of saliency map is contingent upon feedback from pIPS.•The non-graded manner of saliency map is innate to V1.•Awareness-dependent mapping of saliency reconciles previous contradictory findings. The allocation of exogenously cued spatial attention is governed by a saliency map. Yet, how salience is mapped when multiple salient stimuli are present simultaneously, and how this mapping interacts with awareness remains unclear. These questions were addressed here using either visible or invisible displays presenting two foreground stimuli (whose bars were oriented differently from the bars in the otherwise uniform background): a high salience target and a distractor of varied, lesser salience. Interference, or not, by the distractor with the effective salience of the target served to index a graded or non-graded nature of salience mapping, respectively. The invisible and visible displays were empirically validated by a two-alternative forced choice test (detecting the quadrant of the target) demonstrating subjects’ performance at or above chance level, respectively. By combining psychophysics, fMRI, and effective connectivity analysis, we found a graded distribution of salience with awareness, changing to a non-graded distribution without awareness. Crucially, we further revealed that the graded distribution was contingent upon feedback from the posterior intraparietal sulcus (pIPS, especially from the right pIPS), whereas the non-graded distribution was innate to V1. Together, this awareness-dependent mapping of saliency reconciles several previous, seemingly contradictory findings regarding the nature of the saliency map.